Penggunaan E-Bookmik dalam Meningkatkan Kualitas Pembelajaran Pendidikan Agama Islam di MI Negeri 1 Jombang - Miftakhur Rochmah; Khoirotul Idawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Education is a major pillar in sustainable community development. In this digital era, information and communication technology (ICT) has changed the learning paradigm, opening up new opportunities to improve the quality of education. One of the prominent innovations is the use of E-Bookmik as a learning tool in schools. The use of E-Bookmik has great potential to improve the quality of student learning. E-Bookmik allows easier access to learning materials, provides multimedia content, and facilitates interactivity in learning. However, to ensure the success of the implementation of E-Bookmik, effective curriculum management is needed. To describe this research, the author uses a qualitative approach with a case study research type and is supported by data collection techniques through observation, interviews and documentation. After conducting research based on the approaches and types of research mentioned, as well as the theories used, it emerged that the use of E-Bookmik has been implemented well, in addition EBookmik can help facilitate access to teaching materials and make learning more interesting. And students can learn anytime and anywhere. Student learning outcomes increase in understanding and active involvement. E-Bookmik also helps teachers compile and update teaching materials more efficiently, and supports effective and sustainable learning. The use of E-Bookmik in Islamic Religious Education Subjects has great potential to improve the quality of learning. Students are more enthusiastic and understand the material quickly.